Economic relevance of widening access to higher education in Nigeria (2010)
This paper explored the economic benefits of widening access to higher education in Nigeria. Available evidence from theoretical analysis and various data obtained show that higher education contributes to both society and individual economic wellbeing. These are manifested in the form of increase in productivity and output, as well as in earning profiles of \ recipients among other benefits. Other findings show that in spite of the global rapid growth in tertiary education development, most Sub-Saharan African countries (Nigeria included) still lag behind in terms of access to higher education and human development index. In Nigeria, out of over 140 million population (2006 census figures), only 6% (7.50 males and 4.50 females) had higher education. The implication is that except there is a deliberate effort to widen access to higher education in Nigeria, the dream of attaining economic freedom may be difficult. Nevertheless, the paper concludes that although investing in human beings is important at every stage of development, the returns accruable to society from investing in higher education are always higher. It therefore recommends that greater access to higher education be provided in order to ensure economic growth and development